Recommendations for the creation and operation of maternal milk banks in Spain - Javier Calvo; Nadia Raquel García Lara; María Gormaz; Manuela Peña; María José Martínez Lorenzo; Pilar Ortiz Murillo; Josep Maria Brull Sabaté; Carmen María Samaniego; Antoni Gayà (Elsevier, 2018)
It is widely agreed that the best source of nutrition for the newborn is the milk of their own mothers. In those cases where it is not available, especially in very premature and/or very low birth weight infants, as well as other sick newborns, the preferred choice before formula is human milk provided by selected donors. This indication is supported by the highest international bodies dedicated to the health of the child population, including the World Health Organisation as well as the main national and international scientific societies in the field of Paediatrics.Milk banks are health institutions responsible for the collection, processing and distribution of donated human milk. Currently, there are 14 human milk banks operating in Spain, grouped in the Spanish Association of Human Milk Banks, created in September 2008.In order to homogenise the criteria and to unify the working methods of the different milk banks, the Spanish Association of Human Milk Banks has developed standards to harmonise the protocols, and to serve as a guide for the start-up of new milk banks in the Spanish territory. These standards, set out in the present article, range from the donor selection and the evaluation process to the collection, processing, storage, and distribution of donor human milk. Resumen: La mejor alimentación para un recién nacido es la leche de su propia madre. En aquellos casos en los que esta no está disponible, especialmente en los recién nacidos muy prematuros o de muy bajo peso al nacer, así como en otros recién nacidos enfermos, el alimento de elección es la leche materna de donantes seleccionadas, antes que la fórmula artificial. Esta indicación está respaldada por los máximos organismos internacionales dedicados a la salud de la población infantil, como la Organización Mundial de la Salud, así como las principales sociedades científicas nacionales e internacionales en el ámbito de la Pediatría.Los bancos de leche surgen como instituciones sanitarias responsables de la gestión de las donaciones, del procesamiento y de la distribución de leche materna donada. Actualmente existen 14 bancos de leche materna en España, agrupados en la Asociación Española de Bancos de Leche Humana, creada en septiembre de 2008.Con el fin de homogeneizar los criterios y unificar los métodos de trabajo, la Asociación Española de Bancos de Leche Humana ha elaborado unos estándares para armonizar los protocolos de los diferentes bancos y para que sirvan de guía para la puesta en marcha de nuevos bancos de leche en el territorio español. Dichos estándares, presentados en este artículo, abarcan desde el proceso de selección y evaluación de la donante hasta la recogida, el procesamiento, el almacenamiento y la distribución de leche materna de donante.